Causes of death in patients with locally advanced head and neck cancer treated with radiotherapy and systemic therapy - Zapata Martínez, Irene; Álvarez-Pérez, Martína; Hidalgo, R.; Pajares, Bella; García Anaya, María Jesús; Toledo Serrano, María Dolores; Trigo, Jose Manuel; Lupiáñez Pérez, Yolanda; Medina Carmona, Jose Antonio; Gómez-Millán Barrachina, Jaime (BMC Springer Nature, 2019)
Background: To investigate the incidence of non-cancer mortalities and prognostic factors associated with competitive causes of death in a homogeneous cohort of patients with locally advanced head and neck cancer treated with radiotherapy and systemic treatment. Methods: This study included 284 patients with locally advanced head and neck cancer treated with radiotherapy and systemic treatment between 2005 and 2017. The cumulative incidence of death associated with tumour, second tumours, treatment, side effects and comorbidity was calculated. A Fine and Gray regression model was used to investigate factors associated with cancer and competitive mortality. Results: The cumulative incidence of tumoral death at 5 and 10 years were 35 and 47% respectively, whereas the cumulative incidence of competitive mortality were 10 and 12% respectively. In the multivariate analysis, age and comorbidity were independent factors for non-cancer mortality. Patients with a high risk of non-cancer mortality presented a cumulative incidence of 17.3% at 5 years and 18.4% at 10 years. Conclusions: This study demonstrated a high incidence of competing mortality in older patients with comorbidities. Non-cancer deaths should be considered when selecting patients for combination therapies and in the study design ofclinical trials.
Keywords: Enfermos de cáncer - Mortalidad; Competitive mortality; Non-tumoral death; Head and neck cancer